Increasing Students' Learning Activity Through a Differentized Learning Approach Using the Project Based Learnig Model in Primary Schools - Zulkhi, Muhammad Dewa; Destrinelli, Destrinelli; Indryani, Indryani (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the Study: This research aims to explore the application of a differentiated learning approach using the Project-Based Learning (PjBL) model in IPAS (Integrated Science) lessons to enhance student engagement and activity in Class IV at elementary school 31/IV. The study addresses the issue of low student engagement in learning activities, acknowledging the diverse learning needs of students. Methodology: The study employs Classroom Action Research (CAR) with data collection techniques including observations, interviews, and documentation. The research subjects consist of 16 male and 7 female students, totaling 23 participants. Data were gathered through direct classroom observations and documented records during the learning sessions. Main Findings: The findings reveal a significant improvement in student engagement. In the first cycle, the average percentage score for student activity was 62.34%, which increased to 81.40% in the second cycle. These results indicate that the differentiated learning approach, coupled with the PjBL model, effectively enhances student participation and activity in learning. Novelty/Originality of this Study: This research introduces a novel integration of differentiated learning with the PjBL model, offering a tailored educational experience that caters to diverse learning styles and needs. By allowing students to engage creatively and produce tangible projects, the approach fosters increased motivation and active participation. The study not only demonstrates the efficacy of this combined method in improving student engagement but also provides a framework for applying differentiated and project-based learning in various educational contexts. This innovative approach holds promise for transforming traditional teaching methods and enhancing student learning experiences.